tìm GTLN, GTNN của các biểu thức sau: a, A=x^2 – 3x + 5 b, B= (x-1)(x+3)(x+2)(x+6) + 2013 GIÚP MÌNH VỚI MÌNH CẦN GẤP!!!!!!!!!!!!!!!!

Question

tìm GTLN, GTNN của các biểu thức sau:
a, A=x^2 – 3x + 5
b, B= (x-1)(x+3)(x+2)(x+6) + 2013
GIÚP MÌNH VỚI MÌNH CẦN GẤP!!!!!!!!!!!!!!!!

in progress 0
1 năm 2021-08-09T23:32:45+00:00 1 Answers 120 views 0

$$\begin{array}{l} a)\,\,\min A = \frac{{11}}{4} \Leftrightarrow x = \frac{3}{2}\\ b)\,\,\min B = 1977 \Leftrightarrow \left[ \begin{array}{l} x = 0\\ x = – 5 \end{array} \right. \end{array}$$
$$\begin{array}{l} a)\,\,A = {x^2} – 3x + 5\\ A = {x^2} – 2x.\frac{3}{2} + \frac{9}{4} – \frac{9}{4} + 5\\ A = {\left( {x – \frac{3}{2}} \right)^2} + \frac{{11}}{4}\\ \Rightarrow A \ge \frac{{11}}{4}\\ \Rightarrow \min A = \frac{{11}}{4} \Leftrightarrow x = \frac{3}{2}\\ b)\,\,B = \left( {x – 1} \right)\left( {x + 3} \right)\left( {x + 2} \right)\left( {x + 6} \right) + 2013\\ \,\,\,\,\,\,B = \left( {x – 1} \right)\left( {x + 6} \right)\left( {x + 3} \right)\left( {x + 2} \right) + 2013\\ \,\,\,\,\,\,B = \left( {{x^2} + 5x – 6} \right)\left( {{x^2} + 5x + 6} \right) + 2013\\ Dat\,\,t = {x^2} + 5x\\ \Rightarrow B = \left( {t – 6} \right)\left( {t + 6} \right) + 2013\\ \,\,\,\,\,\,B = {t^2} – 36 + 2013\\ \,\,\,\,\,\,B = {t^2} + 1977\\ \Rightarrow B \ge 1977\\ \Rightarrow \min B = 1977 \Leftrightarrow t = 0\\ \Rightarrow {x^2} + 5x = 0 \Leftrightarrow \left[ \begin{array}{l} x = 0\\ x = – 5 \end{array} \right. \end{array}$$